1997
DOI: 10.1042/cs0920075
|View full text |Cite
|
Sign up to set email alerts
|

Brisk Walking Reduces Calcaneal Bone Loss in Post-Menopausal Women

Abstract: 1. This study examined the influence of brisk walking on skeletal status in post-menopausal women. 2. Subjects were 84 healthy women aged 60-70 years. Who were previously sedentary and at least 5 years post-menopausal. Subjects were randomly assigned to walking (n = 43) and control (n = 41) groups. Walkers followed a 12-month, largely unsupervised programme of brisk walking. The bone mineral density of the lumbar spine, femoral neck and calcaneus and broadband ultrasonic attention of the calcaneus were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 22 publications
3
73
0
1
Order By: Relevance
“…Presumably, snow shoveling and various activities performed in training clothes results higher strain on the femoral neck than activities such as walking and bicycling. These results have also been confirmed in clinical studies, in which high-impact training two to three times per week was found to increase BMD in premenopausal women; [17,20,21] however, the effects of this type of physical activity on BMD in postmenopausal women are more modest [22,36,37]. Daly et al studied the association between lifetime sport and leisure activity participation and bone characteristics in older men and showed that long-term regular participation in weightbearing sport and leisure activities was an important determinant of bone size, quality, and strength at the loaded sites [23].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Presumably, snow shoveling and various activities performed in training clothes results higher strain on the femoral neck than activities such as walking and bicycling. These results have also been confirmed in clinical studies, in which high-impact training two to three times per week was found to increase BMD in premenopausal women; [17,20,21] however, the effects of this type of physical activity on BMD in postmenopausal women are more modest [22,36,37]. Daly et al studied the association between lifetime sport and leisure activity participation and bone characteristics in older men and showed that long-term regular participation in weightbearing sport and leisure activities was an important determinant of bone size, quality, and strength at the loaded sites [23].…”
Section: Discussionsupporting
confidence: 69%
“…Some studies have also shown an association between weightbearing physical activity and BMD in middle-aged women and men [17][18][19][20][21]. These studies have reported either a higher BMD in physically active pre-and postmenopausal women *Address correspondence to this author at the Department of Surgical and Perioperative Sciences, Sports Medicine, Umeå University, Umeå, Sweden; Tel: +46-90-7865000; Fax: +46-90-135692; E-mail: taru.tervo@idrott.umu.se compared to inactive women in this same age group [17][18][19][20][21] or less bone loss in physically active women compared to inactive women [21,22]. Only a few studies have investtigated the association between physical activity and BMD in non-athletic middle-aged men [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Walking and running, either overground or on a treadmill are recommended for the health of the general population [9], with benefits including reduced body fat, lowered resting heart rate and increased maximal oxygen uptake [10]. Walking and running are also recommended for maintaining bone health during ageing [11,12,13,14]. For bone health, it is important to establish the magnitude of mechanical loading and muscle activation generated by walking and running as the intensity of loading encourages skeletal adaptation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Target amounts of walking gradually increased from 60 to 140 min/week over the first 3 months and were maintained at this level thereafter. Adherence was confirmed by improvements in fitness, as reported previously [15]. Dietary Ca intake was evaluated by means of 7-day weighed food inventories using computerized food composition tables (Compeat 4.1, Nutrition Systems, UK) at baseline and after 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found significant responses in BMD and broadband ultrasonic attenuation (BUA) at the calcaneus to a 1-year randomized intervention trial of brisk walking in healthy British women aged 60–70 years [15]. Therefore, in this study, we compared these responses in BMD and BUA to the brisk walking programme between VDR genotypes to examine any interaction between the effect of the exercise on bone measurements and VDR polymorphism.…”
Section: Introductionmentioning
confidence: 99%